Central-Moment Discrete Boltzmann Method for Reactive Flows (Communications in Computational Physics, 2025)
A central-moment discrete Boltzmann method (CDBM) is proposed for reactive flows, accommodating adjustable specific heat ratios and Prandtl numbers. Inthe framework of CDBM, a unified set of kinetic equations is used to delineate bothmacroscopic quantities and higher-order central moments. Via these central moments,the nonequilibrium effects that are directly related to the thermal fluctuation beyondconventional hydrodynamic governing equations can be quantified. Moreover, thediscrete Boltzmann equation of the CDBM is simpler than that of previous multiple-relaxation-time DBMs, owing to the elimination of the additional term in the DBM.Furthermore, this method is capable of modeling supersonic compressible reactiveflows characterized by high Mach numbers. The model is verified through simulations encompassing sound waves, shock waves, thermal Couette flows, regular shockreflections, and supersonic reactive waves.